Monetary and Macroeconomic Determinants of Tax Revenue in Sub-Saharan Africa - Omodero, Cordelia Onyinyechi (Ekonomika, 2025)
The challenge of tax collection in rising economies cannot be overstated. These economies have had certain economic setbacks as a result of a lack of a domestic revenue base, tax evasion, and macroeconomic and monetary issues hindering tax revenue growth. This study critically examines the key aspects influencing the tax revenue increase and collection in Sub-Saharan Africa. The dependent variable is the tax revenue, and the monetary and macroeconomic factors that influence it are inflation, income per person, foreign direct investment inflows, broad money supply, and trade openness. These characteristics are shared by several countries in Sub-Saharan Africa. The study uses the Vector Error Correction Model to analyze secondary data from the World Bank Development Indicators for the period of 1990–2023. The findings of this research show that inflation and foreign direct investment inflows have a negative association with tax revenue in the long run, but both have a significant positive impact on the tax revenue in the short term. Other factors, including the broad money supply, GDP per capita, and trade openness, have a negative but insignificant association with tax revenue. The study advises a shift in financial policy to lower inflation and increase the overall money supply. Again, a friendly business climate is required to encourage the free movement of business investment and international commerce in sub-Saharan African regions.